Velvet was the night ebook - Moreno-Garcia, Silvia (2021)
GOOD MORNING AMERICA BUZZ PICK • From the New York Times bestselling author of Mexican Gothic comes a simmering historical noir about a daydreaming secretary, a lonesome enforcer, and the mystery of the missing woman they’re both desperate to find. ONE OF THE BEST BOOKS OF THE YEAR: The New York Times Book Review, NPR, The Washington Post, The Boston Globe, New York Public Library, Milwaukee Journal Sentinel, BookPage, She Reads, Library Journal • “An adrenalized, darkly romantic journey.”— The Washington Post Mexico in the 1970s is a dangerous country, even for Maite, a secretary who spends her life seeking the romance found in cheap comic books and ignoring the activists protesting around the city. When her next-door neighbor, the beautiful art student Leonora, disappears under suspicious circumstances, Maite finds herself searching for the missing woman—and journeying deeper into Leonora’s secret life of student radicals and dissidents.  Mexico in the 1970s is a politically fraught land, even for Elvis, a goon with a passion for rock ’n’ roll who knows more about kidney-smashing than intrigue. When Elvis is assigned to find Leonora, he begins a blood-soaked search for the woman—and his soul.   Swirling in parallel trajectories, Maite and Elvis attempt to discover the truth behind Leonora’s disappearance, encountering hitmen, government agents, and Russian spies. Because Mexico in the 1970s is a noir, where life is cheap and the price of truth is high.